SYNCHRONOUS AND BLENDED LEARNING METHODS IN ANATOMY PRACTICUM DURING THE PANDEMIC - Saharnauli Janna Verawaty Simorangkir; Novita Hasiani Simanjuntak (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Since the beginning of the pandemic Covid 19, all educational institutions have switched offline learning methods to e-learning, including the Faculty of Medicine, University of HKBP Nommensen. One learning method that has switched to an online method is anatomy practicum. The blended learning method is more effective than the synchronous method to be applied to online Anatomy practicums. The purpose of this study was to test the effectiveness of synchronous and blended learning in the implementation of anatomy practicum.Methods: This research was a quasi experimental research. The research sample was all UHN medical students batch 2020. The number of samples were 81 people. The data collection instruments were the AMS questionnaire and the pretest and posttest questions.Results: The results of the bivariate analysis showed an increase in posttest results in both groups. The difference in delta values in the blended method group was higher than the synchronous group and the difference was significant. The results of the analysis for the questionnaire scores showed that there was no significant difference in the level of internal and external motivation between the two groups.Conclusion: The blended learning method is more effective than the synchronous method to be applied to online Anatomy practicums.